2022
DOI: 10.5935/1984-0063.20210033
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Turkish version of the Anxiety and Preoccupation about Sleep Questionnaire in clinical and non-clinical samples

Abstract: Objectives The aim of the study was to investigate the psychometric properties of the Turkish version of Anxiety and preoccupation about sleep questionnaire (APSQ) in clinical and non-clinical samples. Material and Methods Two samples (141 university students and 42 patients with major depressive disorders) completed Turkish APSQ, the Pittsburgh sleep quality index (PSQI), the insomnia severity index (ISI) and the sociodemographic data form. Content validity analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…We accepted the following values for fit index values: χ 2 /df (chisquared/degree of freedom) less than 5.0, comparative fit index (CFI) greater than 0.90, Tucker-Lewis index (TLI) greater than 0.90, and a standardized root-mean square residual (SRMR) close to or below 0.08 [29][30][31]. Reliability values above 0.70 and items with a factor load > 0.30 were interpreted as meaningful and were accepted [32,33]. A p-value of less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…We accepted the following values for fit index values: χ 2 /df (chisquared/degree of freedom) less than 5.0, comparative fit index (CFI) greater than 0.90, Tucker-Lewis index (TLI) greater than 0.90, and a standardized root-mean square residual (SRMR) close to or below 0.08 [29][30][31]. Reliability values above 0.70 and items with a factor load > 0.30 were interpreted as meaningful and were accepted [32,33]. A p-value of less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Tang and Harvey developed the scale in 2004 to measure sleep-related anxiety. 42 Higher scores represent more significant insomnia-related anxiety. In 2022, Uygur et al 42 adapted APSQ to the Turkish language.…”
Section: Instruments For Adultsmentioning
confidence: 99%
“… 42 Higher scores represent more significant insomnia-related anxiety. In 2022, Uygur et al 42 adapted APSQ to the Turkish language. The Turkish APSSQ has robust psychometric properties and an excellent internal consistency coefficient (0.95).…”
Section: Instruments For Adultsmentioning
confidence: 99%
“…The Kaiser-Meyer-Olkin value (0.850), Bartlett's test of sphericity (χ 2 = 1386.47, p < 0.001), and determinant value (0.026) (Table 3) suggested the suitability of the data for exploratory factor analysis. 44,45 Parallel analysis results (Table 3) suggested that only one factor had an eigenvalue above 1 (3.742). A scree plot with a reduced correlation matrix (Supplementary Figure 1) showed similar results.…”
Section: Factor Analysismentioning
confidence: 99%